Pure iron and nickel for new structural reactor materials - Pylypenko, M.M.; Stadnik, Yu.S.; Drobyshevska, A.O. (Вопросы атомной науки и техники, 2019)
The refining processes of iron and nickel from metal and gas impurities by physical methods in vacuum are considered. The effectiveness of using electron-beam melting for purification of these metals is shown. Iron and nickel in a purity of more than 99.98 and 99.994 wt.% respectively have been produced. Розглянуто процеси рафінування заліза і нікелю від металевих і газових домішок фізичними методами у вакуумі. Показана ефективність використання електронно-променевої плавки для очищення цих металів. Отримано зразки заліза і нікелю чистотою понад 99,98 і 99,994 мас.% відповідно. Рассмотрены процессы рафинирования железа и никеля от металлических и газовых примесей физическими методами в вакууме. Показана эффективность использования электронно-лучевой плавки для очистки этих металлов. Получены образцы железа и никеля чистотой более 99,98 и 99,994 мас.% соответственно.